In Situ Enzymatic Conversion of Nannochloropsis oceanica IMET1 Biomass into Fatty Acid Methyl Esters ... - Wang, Yao; Lee, Yi-Ying; Santaus, Tonya; Newcomb, Charles E.; Liu, Jin; Geddes, Chris; Zhang, Chengwu; Hu, Qiang; Li, Yantao (Springer, 2017)
Conventionally, production of methyl ester fuels from microalgae occurs through an energy-intensive two-step chemical extraction and transesterification process. To improve the energy efficiency, we performed in situ enzymatic conversion of whole algae biomass from an oleaginous heterokont microalga Nannochloropsis oceanica IMET1 with the immobilized lipase from Candida antarctica. The fatty acid methyl ester yield reached 107.7% for dry Nannochloropsis biomass at biomass to t-butanol to methanol weight ratio of 1:2:0.5 and a reaction time of 12 h at 25 °C, representing the first report of efficient whole algae biomass conversion into fatty acid methyl esters at room temperature. Different forms of algal biomass including wet Nannochloropsis biomass were tested. The maximum yield of wet biomass was 81.5%. Enzyme activity remained higher than 95% after 55 days of treatment (equal to 110 cycles of reaction) under the conditions optimized for dry algae biomass conversion. The low reaction temperature, high ...